Effect of a self-determination theory-based communication skills training program on physiotherapists' psychological support for their patients with chronic low back pain: A randomized controlled trial - Murray, A.; Hall, A.; Williams, G.; Mcdonough, S.; Ntoumanis, Nikos; Taylor, I.; Jackson, B.; Matthews, J.; Hurley, D.; Lonsdale, C. (W.B. Saunders, 2015)
Objective: To examine the effects of communication skills training on physiotherapists' supportive behavior during clinical practice. Design: Randomized trial. Setting: Hospital outpatient physiotherapy clinics. Participants: Physiotherapists (N=24) and patients (N=24) with chronic low back pain. Interventions: Two hospital clinics were randomly assigned to the intervention arm. Physiotherapists (n=12) received 8 hours of communication skills training focused on supporting patients' psychological needs. Physiotherapists (n=12) from 2 other hospital clinics formed a waitlist control arm. Main Outcome Measures: Verbal communication between each physiotherapist and a patient was recorded on an audiotape, and independent, blinded raters used the Health Care Climate Questionnaire to assess physiotherapists' needs-supportive behavior (primary outcome). Results: Independent raters' Health Care Climate Questionnaire scores favored the intervention arm (Cohen's d=2.27; P<.01). Conclusions: Compared with controls, independent ratings demonstrated that physiotherapists who completed the Communication style and exercise compliance in physiotherapy training were found to provide greater support for patients' needs in a single assessed session. Long-term maintenance of this needs-supportive behavior should be examined.